Presence of Myeloperoxidase in Lamellar Tissue of Horses Induced by an Euglycemic Hyperinsulinemic Clamp - Storms, Nazare; Medina Torres, Carlos; Franck, Thierry; Sole Guitart, Albert; de la Rebière, Geoffroy; Serteyn, Didier (Frontiers in Veterinary Science, 2022)
Laminitis is a pathology of the equine digit leading to a failure of the dermo-epidermal interface. Neutrophil activation is recognized as a major factor in SIRS-associated laminitis. Less is known about the role of neutrophil activation in laminitis associated with metabolic disorders. The aim of this descriptive study was to observe whether myeloperoxidase is increased in the laminae during early stage laminitis in three horses subjected to a prolonged euglycemic hyperinsulinemic clamp (pEHC). After 48 hours of pEHC-treatment, horses were sub-jected to euthanasia. Two healthy horses are used as control. Histological sections of lamellar tissue from all horses were immunohistochemically stained for myeloperoxidase and counterstained with hematoxylin-eosin. Histopathological changes that characterize insulin-induced laminitis and increased presence of myeloperox-idase, especially in the dermal lamellae, were increased in histologic sections of pEHC-treated horses. Neu-trophil myeloperoxidase release may contribute to the pathophysiology of endocrinopathic laminitis.